1.1 THz tenth harmonic mixer based on planar GaAs Schottky diode. Issue 11 (29th April 2019) - Zhang, Bo; Lv, Xiaolin; He, Jie; Xing, Dong; Fan, Yong; Chen, Xiaodong
Abstract : Here, the tenth harmonic mixing technology based on planar GaAs Schottky diode is first proposed for the 1.1 terahertz (THz) frequency conversion module. The first higher order mode cut‐off frequency of the suspended microstrip line has been investigated to determine the appropriate cross‐sectional dimension of transmission line shield cavity in the radio frequency (RF) circuit portion. The height of shield cavity of transmission line is designed to be discontinuous in order to facilitate the assembly of the diode. A modelling approach combining field and circuit is used to achieve joint simulation of linear passive structure and diode non‐linear characteristics. The simulation results show that the frequency conversion loss of this mixer is <55 dB in the RF frequency range of 1.03–1.154 THz, and the best frequency conversion loss is 50 dB at RF of 1.098 THz.